2023
DOI: 10.2337/dc23-1355
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter Prospective Evaluation of the Benefits of Two Advanced Hybrid Closed-Loop Systems in Glucose Control and Patient-Reported Outcomes in a Real-world Setting

Pilar Isabel Beato-Víbora,
Ana Chico,
Jesus Moreno-Fernandez
et al.

Abstract: OBJECTIVE Advanced hybrid closed-loop systems (AHCL) have been shown to improve glycemic control and patient-reported outcomes in type 1 diabetes. The aim was to analyze the outcomes of two commercially available AHCL in real life. RESEARCH DESIGN AND METHODS A prospective study was performed, including adolescents and adults with type 1 diabetes, AHCL naïve, from 14 centers, who initiated the use of MM780G with SmartGuard or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We have read with great interest in Diabetes Care the results from the recent multicenter real-world prospective study conducted by Beato-V ıbora et al (1), comparing glucose and patient-reported outcomes 3 months after advanced hybrid closed-loop (AHCL) insulin delivery system initiation (either Medtronic Smart-Guard 780G and Tandem T-Slim Control-IQ users). The authors concluded, based on continuous glucose monitoring from 150 participants (87% of whom are aged $25 years), that the AHCL systems provided significant and similar improvement in glucose control, partly in line with a recent publication from our group (2).…”
mentioning
confidence: 99%
“…We have read with great interest in Diabetes Care the results from the recent multicenter real-world prospective study conducted by Beato-V ıbora et al (1), comparing glucose and patient-reported outcomes 3 months after advanced hybrid closed-loop (AHCL) insulin delivery system initiation (either Medtronic Smart-Guard 780G and Tandem T-Slim Control-IQ users). The authors concluded, based on continuous glucose monitoring from 150 participants (87% of whom are aged $25 years), that the AHCL systems provided significant and similar improvement in glucose control, partly in line with a recent publication from our group (2).…”
mentioning
confidence: 99%